DIMENSION OF KINDNESS IN THE STUDENT POPULATION - Simonovic, Maja M; Vukojčić, Natalija; Stojanović, Nikola; Nikolić, Gordana (Acta medicae Medianae, 2024)
The acts of helping others are a manifestation of a personal dimension called kindness, which is of particular importance in medicine. The capacity of people who work in medicine to show kindness is one of the factors that determines the future course of treatment. The primary goal of the research is to determine the presence of the category of kindness in the group of students of the Faculty of Medicine and the group of students from other faculties of the University of Niš and to determine whether there is a difference in the category of kindness between the two groups of students. A total of 230 subjects filled out an online questionnaire. The multidimensional instrument Kindness scale was used for the assessment of kindness. Data are presented as mean score values for each aspect of kindness, as well as maximal and minimal values. A comparison between the two groups was performed using Student’s t-test for two independent large samples. The results did not show any difference in any of the studied dimensions of kindness in the groups of respondents. The results provided insight into the nature of kindness, its obstacles, and its importance, and they indicated the necessity of thinking about the dimension of kindness while working with students and in everyday clinical practice.